Principle of localization of solutions of the Cauchy problem for one class of degenerate parabolic equations of Kolmogorov type - Litovchenko, V. A.; Strybko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
In the case where initial data are generalized functions of the Gevrey-distribution type for which the classical notion of equality of two functions on a set is well defined, we establish the principle of local strengthening of the convergence of a solution of the Cauchy problem to its limit value as $t → +0$ for one class of degenerate parabolic equations of the Kolmogorov type with $\overrightarrow{2b}-$parabolic part whose coefficients are continuous functions that depend only on $t$.